Health risk assessment of trace metals from spinach grown on compost-amended soil. Issue 13 (10th November 2018) - Saleem, Fouzia; Riaz, Umair; Aziz, Humera; Murtaza, Ghulam; Saifullah,; Naveed, Muhammad; Shahid, Muhammad; Murtaza, Behzad
Abstract: The present study evaluates the impact of two commercially available composts on the accumulation of trace metals in soil and spinach, and their potential health risks to humans. The treatments were municipal waste compost (MC) and agricultural waste compost (AC) applied at 0.5, 1.0, and 1.5% (w/w)—with the recommended dose of NPK fertilizers (50:25:0) as a control. Trace metals concentrations (Cd, Cu, Pb, and Zn) in both composts were below the threshold level. The improved spinach yield with MC was 2.77, 16.88, and 42.34% and with AC 5.53, 17.19, and 53.38% over the control at 0.5, 1.0, and 1.5% levels, respectively. Concentrations of Cd, Cu, Pb, and Zn in spinach leaves were found higher than permissible limits at all levels of MC. However, Cu, Pb, and Zn were recorded within safe limits with AC except for Cd (which was at 1.0% and 1.5%). The daily intake of trace metals and their health risk index were found higher at elevated levels (1.0% and 1.5%) of MC and AC. The results revealed that besides all the benefits of commercial composts, they must be regularly monitored to avoid buildup of trace metals in soils and plants as well as their potential risks to human health at higher dose.